Law or morality: which is more important? (2005)
The painstaking controversy opened by Dr. Villegas invites to critically inquire about the results of our work Indicators of Citizen Coexistence. From its title it poses a crucial question: Subject to morality or law?To summarize, the authoress of this comment questions our definition of morality and its consequences and accuses us of two things: to assume a position in favor of morality relativism and to promote an excessive conformance with law.To examine and collate her points of view, we will consider in this article: 1) our characterization of morality in terms of auto-regulation, 2) the difference between pluralism and relativism, 3) the hierarchy between law and morality, 4) the role of morality reflection and the need to overturn (and indeed to recognize it as its main ingredient) the tensions between law and morality towards the democratic practices. Besides (part ii) we will attend the invitation to explore a relevant “prescriptive” question: Will it be better to be almost-compliant or compliant? (question associated with the suspicion of those who are in stage 5 or 6 of Kohlberg are almost-compliant).